A dinosaur's day - Thomson, Ruth, 1949- (New York : Dorling Kindersley Pub., 2000)
A gentle Triceratops forgets to stay with the herd and has to use his sharp horns to fight a Tyrannosaurus.
SJ 11/00
0306
Keywords: Dinosaurs -- Fiction